Comparative analysis of matrix metalloproteinases by zymography in patients with colorectal carcinoma - Večurkovská, Ivana; Stupák, Marek; Kaťuchová, Jana; Roškovičová, Veronika; Mašlanková, Jana (Physiological research, 2023)
Zymography is an electrophoretic method in which proteins are separated in a polyacrylamide gel in the presence of sodium dodecyl sulfate (SDS-PAGE). This method is used for the detection of enzymatic activity and molecular characterization of proteins. In contrast to the standard SDS-PAGE method, a substrate is incorporated into the gel during zymography, which is subsequently cleaved by target proteases. Many studies have focused on the development and progression of inflammatory diseases affecting the gastrointestinal tract, emphasizing the role of the largest group of proteases, matrix metalloproteinases (MMPs). The most used classification of this group of enzymes (by researchers in MMP biology) is based in part on the historical evaluation of the substrate specificity of MMPs and in part on the cellular localization of MMPs. MMPs are thus classified into the groups of collagenases, gelatinases, stromelysins, matrilysins, membrane-type MMPs (MT-MMPs), and others. An important group of MMPs are gelatinases which are involved in the breakdown of collagen type IV and gelatin of extracellular matrix and participate in the regulation of various physiological or pathological processes such as morphogenesis, angiogenesis, tissue repair, cirrhosis, arthritis, and metastasis. The present study's objective was to determine the amount of active MMP-9 and MMP-2 forms in tissue samples using zymography. The patient group was according to histology findings divided into the benign tumor (control) group (8 patients), and the malignant tumor group (24 patients). The respondents in the malignant tumor group were further divided according to the standard TNM classification. The results of this study confirmed that MMP-2, unlike MMP-9, can be used as a prognostic biomarker of CRC, because only the expression of active MMP-2 confirmed statistically significant differences between individual stages of CRC. Moreover, MMP-2 seems to play a more important role in higher stages of CRC. Substantial disparities in the determination of active MMPs between the observed groups support the assumption for the integration of zymography into clinical diagnostics of CRC together with molecular and other studies.
Keywords: matrixová metaloproteinasa 2; Humans; extracelulární matrix; kolorektální nádory; lidé; Matrix Metalloproteinase 9; Matrix Metalloproteinase 2; matrixová metaloproteinasa 9; Colorectal Neoplasms; Extracellular Matrix